An overview of the Tigger object-support operating system framework - CAHILL, VINNY (Springer-Verlag, 1996)
This paper describes the motivations for and main features of Tigger -- a framework for the construction of a family of object-support operating systems that can be tailored for use in a variety of different application domains. An important goal of the design of Tigger is that instantiations of the framework should be able to support (a number of) different object models in order to allow a range of object-oriented languages for distributed or persistent programming to be supported without unnecessary duplication of effort. A further goal of the design is that instantiations of the framework should be able to support the same object model in different ways depending on the requirements of the applications to be supported by those instantiations. This paper describes the main features of the Tigger framework that allow these goals to be realised.
Lecture Notes in Computer Science
SOFSEM '96: Theory and Practice of Informatics
PUBLISHED
Berlin/Heidelberg
Keywords: Computer Science